Cold fusion back from the dead. - Mullins, J. (IEEE spectrum)
The US Energy Department has renewed its efforts to investigate the prospects for cold fusion, the supposed generation of thermonuclear energy using tabletop apparatus. While critics say that the extravagant claims behind cold fusion need to be backed with exceptionally strong evidence, there has been a small group of dedicated researches who have continued to conduct investigations. Over the years, a number of groups around the world have reproduced the original Pons-Fleischmann excess heat effect, yielding sometimes as much as 250 percent of the energy put in. It appears that the results of all these research have convinced the DOE to give cold fusion another look.